Application of a Stable Latency Insertion Method for Simulations of Power Distribution Networks - Hang Tan, Kin; Goh, Patrick; Ain, Mohd Fadzil (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
This paper presents an application of a stable implementation of the latency insertion method for simulations of power distribution networks (PDN). Traditionally, simulations of PDNs poses a considerable challenge due to their large circuit sizes. While the latency insertion method can be applied to simulate these networks, the existence of low latency elements results in a more stringent stability criterion which reduces the efficiency of the method. Using the improved formulation, a latency insertion method that is free from the stability criteria is obtained, which results in no limitation on the size of the time step.